A Study to Assess the Knowledge Regarding Corona Virus and Its Management among the People Residing in Pune City - Roma Shinde, Shital Waghmare (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Assessment of public general knowledge on coronavirus and its management is essential todevelop health policies for segregating the spread of disease.Objectives: To assess the level of knowledge regarding Coronavirus among the people residing in Pune city.To identify its predicators Respiratory Syndrome due to Coronavirus.Methods: A survey designed was conducted during April-May 2020, whereas adult (? 18 years old) thepeople residing in pune city were included in the study. Non probablity convience sampling technique wasused. Data was collected by structured questionnaire. Data was processed and analyzed in descriptive andinfrential way.Results: A total 60 samples were recruited (age range18-30 years) the majorities were male and 45% wereuniversity graduate students. Among all interviewees 35% believed that the disease transmission can occursthrough infected birds and animals. As a result the disease has no specific treatment was known by 45% and20% of them denied any role of traditional medicines in preventions and treatment of disease? Participantshad satisfactory knowledge about the disease and its management were.Conclusions: Although effort doneby health professionals in city to educate the people and to expand their awareness about disease, there isknowledge deficit among local public. Future planning and educational interventions should focus on peopleand those who have educational background below the university level.